Geographic Factors Enhancing Banditry and its Impact on Educational Services in Rafi Local Government Area, Niger State, Nigeria (2020–2026) - Dodo, F.; Abdulkadir, A.; Muhammed, M. (Journal of Spatial Information Sciences, 2026)
This study examined the geographic factors that enhance banditry and their impact on educational services in Rafi Local Government Area of Niger State, Nigeria, between 2020 and 2026. The study adopted a descriptive survey research design complemented by Geographic Information System (GIS) and Normalized Difference Vegetation Index (NDVI) spatial analysis techniques. The population of the study was 320,000, comprising teachers, students, parents, community leaders, and security personnel. A sample size of 384 was determined using the Krejcie and Morgan Table. The instrument used for data collection was a questionnaire that was validated by experts and pilot-tested with 50 respondents from Tegina. The reliability of the instrument was determined using Cronbach’s Alpha, which yielded a reliability coefficient of 0.78. Frequency counts were used for data analysis to answer the research questions. The study also utilized a Normalized Difference Vegetation Index (NDVI) map of Rafi Local Government Area to depict vegetation density and identify potential areas favourable to bandit activities. Geographic Information System (GIS) technology was used to map the spatial distribution of terrain within the identified banditry hotspot areas in Rafi LGA, Niger State. The findings revealed that dense forests, poor road networks, and porous community boundaries significantly enhance banditry in Rafi LGA, whereas remote settlements and illegal mining/rural poverty were not identified as major contributing factors. The study also found that banditry negatively affects educational services through increased fear among teachers and students, teacher transfers, reduced student attendance, disruption of teaching and learning activities, and the withdrawal of children from school by parents. The study concluded that geographic factors significantly enhance banditry and undermine educational development. The study recommends that Government and security agencies should increase the deployment of security personnel in identified banditry hotspot areas such as Tegina, Pandogari, and Yakila in order to improve surveillance and rapid response to attacks.